Expression, crystallization and preliminary X-ray crystallographic analysis of DNA-directed RNA polymerase subunit L from Thermococcus onnurineus NA1 - Ho, Thien-Hoang (International Union of Crystallography, 2014)
RNA polymerase (RNAP) plays a crucial role in gene expression in all organisms. It is a multiprotein complex that produces primary transcript RNA. Generally, the basal transcription apparatus in archaea is simpler than the eukaryotic RNA polymerase II counterpart. To understand the structure and function of archaeal RNAP, the TON-0309 gene encoding DNA-directed RNA polymerase subunit L (ToRNAP_L) from Thermococcus onnurineus NA1 was cloned and the protein was overexpressed in Escherichia coli, purified and crystallized. The purified protein was crystallized using the hanging-drop vapour-diffusion method and the crystal diffracted to 2.10 Å resolution. The crystal belonged to the hexagonal space group P6(1)22, with unit-cell parameters a = b = 42.3, c = 211.2 Å. One molecule was present in the asymmetric unit, with a corresponding V (M) of 2.5 Å(3) Da(−1) and a solvent content of 50.0%.